2011
DOI: 10.3324/haematol.2010.039768
|View full text |Cite
|
Sign up to set email alerts
|

Array-based genomic screening at diagnosis and during follow-up in chronic lymphocytic leukemia

Abstract: The online version of this article has a Supplementary Appendix. BackgroundHigh-resolution genomic microarrays enable simultaneous detection of copy-number aberrations such as the known recurrent aberrations in chronic lymphocytic leukemia [del(11q), del(13q), del(17p) and trisomy 12], and copy-number neutral loss of heterozygosity. Moreover, comparison of genomic profiles from sequential patients' samples allows detection of clonal evolution. Design and MethodsWe screened samples from 369 patients with newly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
81
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(87 citation statements)
references
References 43 publications
6
81
0
Order By: Relevance
“…In line with this reasoning, CLL cases with the longest telomeres at diagnosis showed the most pronounced yearly telomere loss. It is noteworthy that similar data showing base line dependent TL alterations by time have been shown in normal blood cells indicating similar mechanisms for telomere maintenance in leukemic and normal cells [16][17][18].Finally, we assessed TL and clonal evolution defined by the acquisition of new copy number aberrations (CNAs) in 47 cases of which 11 were previously found to display clonal evolution [19]. These cases were mainly IGHV unmutated (64% vs. 31% for cases without clonal evolution) and had distinctly shorter TL at diagnosis (average 1,791 U vs. 2,770 U, P 5 0.052).…”
mentioning
confidence: 96%
“…In line with this reasoning, CLL cases with the longest telomeres at diagnosis showed the most pronounced yearly telomere loss. It is noteworthy that similar data showing base line dependent TL alterations by time have been shown in normal blood cells indicating similar mechanisms for telomere maintenance in leukemic and normal cells [16][17][18].Finally, we assessed TL and clonal evolution defined by the acquisition of new copy number aberrations (CNAs) in 47 cases of which 11 were previously found to display clonal evolution [19]. These cases were mainly IGHV unmutated (64% vs. 31% for cases without clonal evolution) and had distinctly shorter TL at diagnosis (average 1,791 U vs. 2,770 U, P 5 0.052).…”
mentioning
confidence: 96%
“…[4][5][6]14 Analyses on larger number of patients and on specific subgroups of patients have now documented a particularly high frequency of NOTCH1 mutation in CLL cases harboring trisomy 12 (+12), one of the cytogenetic alterations recurrently observed in CLL and classically associated with an intermediate prognosis. 15 In this issue of Haematologica, Del Giudice and colleagues document a high frequency of NOTCH1 mutations in CLL cases harboring trisomy 12 as the sole cytogenetic abnormality (30%). 7 Importantly, this study also reveals a significant shortening of survival in the NOTCH1 mutation positive patients, refining the intermediate prognosis of CLL cases with trisomy 12.…”
Section: 2mentioning
confidence: 99%
“…However, gains of 3q and losses of 1p are relatively frequent in MCL but not in CLL. [14][15][16][17] Gains or trisomy of chromosome 3 are also a frequent feature of marginal zone lymphomas (MZL) and diffuse large B-cell lymphoma (DLBCL) of the activated B-cell subtype (ABC). 18,19 These two types of tumors have frequent gains in 18q but ABC-DLBCL also has frequent deletions in 6q, 9p, and 19q not common in MZL.…”
Section: Platformsmentioning
confidence: 99%
“…15,19 In some lymphoid neoplasms, such as CLL and MCL, DNA-array studies have shown that the genomic complexity is an important prognostic parameter independent of other known factors. [15][16][17] Gene expression profiling The microarray technologies have made possible the study of the global GEP of tumors (Table 2). These platforms consist of numerous DNA probes immobilized on a solid surface.…”
Section: Platformsmentioning
confidence: 99%